The problem of meaning in religious discourse (Revista de Investigaciones Universidad del Quindío, 2022)
In this article, I develop an interpretation of religious language, as a discourse that like some languages as ethical, aesthetic and moral, provides significant linguistic, social, and cultural elements to understand the relationship of the subject with history and its culture. To do this, I distance myself from contemporary neo positivist philosophical positions, a movement that tried to reduce language to the analysis of logic, science and mathematics as referents of the world. I propose a resignification of religious language legitimizing its semantic, syntactic and pragmatic validity, to understand the subject, especially from this language and its context. Therefore, I opine that religious language is a linguistic construction, which, like any other language, contains its own rules and structures that show an intention to interpret the world. In order to do this, I will address the following topics: the study of language in contemporary philosophy; logical positivism and the limitations to understanding other languages; and, finally, religious language and its meaning from its linguistic and theoretical components.
Keywords: religious language; religious discourse; pragmatics of religious language; meaning; context